New Twist to Political Corruption in 4th Republic Nigeria given Non- Human Animals Stealing millions: A Case for the Defense of Animal Rights - Osuala, Amaobi Nelson; Nyok, Efio-Ita Effiom (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
Corruption has assumed a new turn in 4th Republic Nigeria, particularly where non-human animals are alleged by human animals to deep their hands into the public tilt for their selfish non-human animal purposes. This is a clear case of hypocrisy on the part of human animals in that, at one instance we contend that non-human animals are inferior to human beings and at the other instance, we affirm though inadvertently that non-human animals are not inferior but equal since they can steal: we, therefore, are unable to steer ourselves out from the dilemma of our ambivalence to arrogate to ourselves a god-like status over non-human animals. We contend that this is another profound inhumane case of violation of non-human animals which is condemnable. We have suggested that the solution to this quagmire is first to admit that nonhuman animals have basic rights like human animals especially when we understand this notion of Rights going beyond its parochial conception. The method we have employed in showing moments of human’s inhumanity to non-human animals is what has been conceived as Ibuanyidanda Philosophy according to which we aver that ihe di nwereisinaodu (anything that exists serves a missing link of reality). We have argued in favour of the thesis that the federal government should allow justice prevails against acts of theft by either civil or public servants.